Kochane depresje młodopolskich mistrzów i epigonów - Strugińska, Karolina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
The article is an attempt to reinterpret melancholy, which is variously expressed in Polish Modernist poetry. The author does not treat it as a mask, which was often worn by the writers of that period presenting them as martyrs, but as a symptom of depressive disturbances from which some of the authors could have sufTered. The author tries to show alleged reasons of depression in biographies of various authors. She also emphasizes the influence of characteristic tendencies of the era on the psychical condition of the authors and its expression in poetry. The work is full of literary examples describing psychological states. It describes typical themes, stylistic means and also shows the ways of depicting psychological states, which are analogous to the symptoms of depression described by Antoni Kępiński.